Calistung-Based Smart Book Media to Increase Student Interest in Learning Mathematics - Salma Febrina Putri; Wahyudi Wahyudi; Arta Ekayanti (STAI Hubbulwathan Duri, 2025)
Low learning interest among Hulu Langat Guidance Studio students has been observed, prompting efforts to enhance engagement through innovative methods. This study investigates the effectiveness of Smart Book media in increasing students' interest in learning. Employing a classroom action research approach, the study followed four stages: planning, implementation, observation, and reflection. Conducted at the Hulu Langat Guidance Studio in Malaysia, the study involved a sample of 10 students. Data were collected through observation and questionnaires over two research cycles, incorporating Smart Book media. The findings revealed a significant improvement in students' learning interest following the implementation of Smart Book media. Questionnaire results indicated that all students categorized their learning interest as